Atypical Mal de Meleda in a Hispanic Patient - Mónica Guevara; Michelle Mafla; Camila Miño (Case Reports in Dermatological Medicine)
Mal de Meleda (MDM) is a rare autosomal palmoplantar keratoderma (PPK) skin disorder (estimated incidence of 1 per 100,000 people) commonly associated with consanguinity and early childhood onset. MDM is characterized by bilateral diffusion of PPK plaques with delimited yellowish lesions that transgredien to the dorsum of the hands and feet. Additional features include nail dystrophy, lichenoid lesions, hyperhidrotic maceration, involvement of the knees and elbows, malodor, fungal superinfections, and digital constrictions. A male patient aged 42 years presented with asymptomatic, chronic, and diffused PPK lesions that progressed to the dorsal surface of the hands and feet, along with knees and elbows involvement. On clinical examination, asymmetrical lesions were observed on the hands, the left palm with yellowish waxy hyperkeratotic plaques, and the right palm with erythematous scaling and hyperkeratotic interphalangeal rings. The soles of the feet presented with yellow waxy hyperkeratotic plaques. In addition, nail dystrophy and loss of dermatoglyphics were observed. Initially, symptomatic topical treatment was established. However, owing to the lack of clinical response, a biopsy was performed, which revealed thickened corneal layer, acanthosis, spongiosis, and perivascular lymphohistiocytic infiltrate. MDM diagnosis was confirmed based on a personal history of consanguinity, clinical presentation with absence of systemic symptoms, and transgredien pattern of the lesions. Systemic treatment with low doses of isotretinoin (10 mg orally everyday) was initiated, and two months later, slight clinical improvement has been observed until date. The present case report describes MDM in a Hispanic patient, who presented with asymmetric PPK lesions on the hands and received isotretinoin treatment.